Quality assured ultrasound simulator training for the detection of fetal malformations - Staboulidou, Ismini; Wüstemann, Max; Vaske, Bernhard; Elsässer, Michael; Hillemanns, Peter; Scharf, Alexander (Acta obstetricia et gynecologica Scandinavica, 2010)
Objective. Sonographic training in obstetrics differs broadly in Germany, although there are clearly defined quality-oriented requirements. In order to improve professional education, a training concept was devised utilizing an ultrasound simulator system. Design. Between October 2004 and May 2006, 100 obstetric ultrasound training courses were held in 12 federal states of Germany. In these daily courses, doctors were trained in the detection of the most common malformations. Sample. One hundred training courses with a total of 1,266 participants. Methods. As a measure of quality assurance, a standardized questionnaire focusing on testing sonographic proficiency before and after the courses was issued in order to analyze the effect of these simulator-based ultrasound courses. Main outcome measures. Effectiveness of the method with reference to its potential role in structured sonographic training. Results. The concept found prevailing approval (90%) at the level of principle, practical implementation, and clinical usefulness. Of the participants, 91% estimated their subjective training effect as good. The questionnaire analysis showed significant improvement. On average, 75.3% of the questions relating to sonographic proficiency were answered correctly at the end of the course as opposed to 48.6% at the beginning. Conclusion. Structured ultrasound training courses based on an ultrasound simulator system seem to be useful for defining a basic standardized quality of training and significantly improving examiners’ skills. This is a suitable additional instrument to improve the education in obstetric ultrasound.